Tłumaczenie biznesowe a środowiskowe –status i rola tłumacza - Krajewska, Katarzyna (Investigationes Linguisticae, 2019)
The aim of this article is to present “business interpreting” as such and to contrast it with conference and community interpreting. The article also discusses various roles interpreters assume in business setting and gives examples of real-life situations where it might be difficult to unambiguously decide what should be expected from an interpreter. A number of questions for further research is also asked.